2013
DOI: 10.1128/aac.01520-12
|View full text |Cite
|
Sign up to set email alerts
|

Azole Susceptibility and Transcriptome Profiling in Candida albicans Mitochondrial Electron Transport Chain Complex I Mutants

Abstract: dMitochondrial dysfunction in pathogenic fungi or model yeast causes altered susceptibilities to antifungal drugs. Here we have characterized the role of mitochondrial complex I (CI) of Candida albicans in antifungal susceptibility. Inhibitors of CI to CV, except for CII, increased the susceptibility of both patient and lab isolates, even those with a resistance phenotype. In addition, in a C. albicans library of 12 CI null mutants, 10 displayed hypersusceptibility to fluconazole and were severely growth inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 46 publications
(64 reference statements)
4
86
0
Order By: Relevance
“…We have also observed that fluorescent BQM coaccumulates in mitochondria with the mitochondrial stain MitoTracker (data not shown). We also observed that several mitochondrial mutants, such as the goa1 and ndh51 null mutants (22,42,43), showed increased resistance to BQM compared to the wild-type control (data not shown). The role of mitochondria in fluconazole susceptibility among Candida spp.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We have also observed that fluorescent BQM coaccumulates in mitochondria with the mitochondrial stain MitoTracker (data not shown). We also observed that several mitochondrial mutants, such as the goa1 and ndh51 null mutants (22,42,43), showed increased resistance to BQM compared to the wild-type control (data not shown). The role of mitochondria in fluconazole susceptibility among Candida spp.…”
Section: Discussionmentioning
confidence: 67%
“…Drug susceptibility testing was carried out in flat-bottom, 96-well microtiter plates (Greiner Bio One) using the broth microdilution protocol according to the Clinical and Laboratory Standards Institute M-27A methods. Growth inhibition of all strains was evaluated in the presence of drugs and reported as percent inhibition of untreated cells as previously described (22). In brief, overnight cultures were prepared in YPD and washed, and ϳ10 3 cells/100 l were inoculated into microtiter wells.…”
Section: Methodsmentioning
confidence: 99%
“…Our published data also correlate a loss of CI with increased susceptibility to fluconazole. 21,22 In this case, we have shown that 10 of 12 CI mutants were hypersusceptible to fluconazole. The two CI subunits that were not hypersusceptible were not associated with a respiration function.…”
Section: Complex I Subunit Proteins As Drug Targetsmentioning
confidence: 92%
“…The two CI subunits that were not hypersusceptible were not associated with a respiration function. 21 Thus, loss of mitochondrial ATP may be a benefit of an inhibitor that could specifically block CI respiration activity and, correspondingly, would ensure a reduction in resistance to antifungals such as the azoles.…”
Section: Complex I Subunit Proteins As Drug Targetsmentioning
confidence: 99%
“…C. albicans cannot undergo loss of mitochon-drial DNA and therefore is considered a "petitenegative" species. However, pharmacological inhibition of mitochondrial complexes involved in respiration and energy production results in higher susceptibility to azoles in this species (Sun et al 2013). The findings that mitochondrial defects are associated with azole resistance in C. glabrata, but susceptibility in C. albicans, suggests complex functional relationships between the azoles activity and mitochondrial function in fungal pathogens.…”
Section: Mitochondrial Defectsmentioning
confidence: 82%